In the footsteps of Alexander the Great: searching for the origins of ancient zooplankton on the wild steppe of Central Asia. (March 2015) - Williams, Mark; Siveter, David J.; Perrier, Vincent; Mikhailova, Elena; Tarasenko, Anna; Salimova, Firuza; Kim, Irina A.
Abstract : Rising above the modern town of Nurata, in Navoiy Province, eastern Uzbekistan is the ancient fortress of Alexander the Great, built as part of Alexander's campaigns to subjugate the Persian‐speaking Sogdian peoples that lived in this province of the Persian Empire in the 4th Centurybc . Alexander passed this way in 327bc, marching his ancient army through this beautiful but desolate landscape, and conquering all before him. His fortress was built in a strategic place at the boundary between fertile agricultural lands and a dry and uncompromising vastness of steppe that lies to the east. From Nurata, about one hour drive by car along a road that cuts eastwards across the desert, is the sleepy town of Jo'sh. In the mountains beyond Jo'sh sits the hamlet of Kanda, a few mud‐brick houses nestling at the head of a small valley where a spring emerges miraculously from a bone‐dry landscape. Hereabouts are telltale signs of ancient marine deposits yielding graptolites from rocks of the Silurian system. And in these rocks are the fossils of tiny arthropods that mark a fundamental shift in the marine arthropod zooplankton 425 million years ago. It is these fossils that we have chased halfway across the world to the steppe of Central Asia.